Review: Climate change resilience disconnect in rural communities in coastal Kenya. A rhetoric communication discord proliferated by COVID-19 pandemic - Ngare, Innocent O.; Gikonyo, Salome W.; Gathuku, George N.; Ogutu, Emma A. (Frontiers in Sustainable Food Systems, 2022)
The world has been hit by consequential pandemics in the past two millennia. The COVID-19 pandemic has taken center stage, paralyzing vulnerable communities in the global south impacted by unprecedented climate vagaries. The focus of this study is COVID-19 and Climate Resilience Communication Rhetoric. In this context, we embed this study in response to the resilience of rural livelihoods to the COVID-19 crisis and climate resilience education communication rhetoric. We posit our review based on the following questions: Has COVID-19 worsened the climate resilience pathway for rural communities in coastal Kenya? Is the COVID-19 pandemic a proxy for climate resilience in rural livelihoods? How does COVID-19 communication rhetoric undermine climate resilience for vulnerable coastal communities in Kenya? Through a resilient theoretical paradigm, we enclose our view based on the existing literature along with climate resilience and COVID-19 proliferation. In light of the current state of COVID-19, the focus has shifted to the pandemic that will cover climate resilience. From the review, climate resilience pathway has been impacted by corona virus with noted funding response variations, in addition, even with the corona virus pandemic, climate resilience communication should be on-going rather than sporadic. Increasing the discursive process about climate change challenges is critical among Kenyan coastal communities. We recommend inclusion of climate resilience communication in existing policy frameworks as a salient solution to notable information discourse bottlenecks.